2004
DOI: 10.1007/s10267-003-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycelial growth characteristics in a split-plate culture of four strains of the genus Suillus

Abstract: A split-plate method with two media in different concentrations in each compartment was applied for the mycelial growth of four strains of Suillus luteus, S. grevillei, S. granulatus, and S. bovinus. As the glucose concentration in the A-side (the side containing higher concentrations of glucose) increased, the mycelial growth in both A-and Bsides (the side containing lower concentrations of glucose) increased. The mycelial density in both sides and B/A ratio (the ratio of the mycelial growth in the B-side to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…We stimulated ECM mycelial growth by different nutritional conditions and found considerably significant differences among the applied in vitro conditions without host plant, which speculate that higher concentrations of nutrients may be the reason of mycelial growth rates inhibition. This phenomenon can be explained by two ways: (i) the mycelial catabolism was suppressed by the higher concentration of nutrients because of osmotic pressure as the ectomycorrhizal fungi do not grow under high osmotic pressure and (ii) presence of high concentration of vitamin and hormones increased the activity of some enzymes which could suppress mycelial growth [23,24]. These kinds of effect were also reported from other scientists with the application of carbohydrate components [25,26].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We stimulated ECM mycelial growth by different nutritional conditions and found considerably significant differences among the applied in vitro conditions without host plant, which speculate that higher concentrations of nutrients may be the reason of mycelial growth rates inhibition. This phenomenon can be explained by two ways: (i) the mycelial catabolism was suppressed by the higher concentration of nutrients because of osmotic pressure as the ectomycorrhizal fungi do not grow under high osmotic pressure and (ii) presence of high concentration of vitamin and hormones increased the activity of some enzymes which could suppress mycelial growth [23,24]. These kinds of effect were also reported from other scientists with the application of carbohydrate components [25,26].…”
Section: Discussionmentioning
confidence: 62%
“…These might be the results due to the variations among the different strains. Therefore, the results also provide evidence that the mycelial appearance not only varies with the culture media but also changes with the fungal species and strains which suggest considerable intraspecific variation among different strains [19,23,24,27].…”
Section: Discussionmentioning
confidence: 88%
“…Murril. Moreover, Hatayama and Ohmasa (2004) showed that many strains of the genera Suillus and Boletinus can grow well at relatively high glucose concentrations (3.33%-10%). The utilization of carbohydrates for growth substrate by T. matsutake in the broadleaf forest is thought to be different from T. matsutake in the pine tree forest.…”
Section: Discussionmentioning
confidence: 98%
“…Ectomycorrhizal fungi are believed to obtain much of the carbon necessary for growth from the host plants through ectomycorrhizae. Recently, Hatakeyama and Ohmasa (2004) have showed that many strains of the genus Suillus and Boletinus can grow well at relatively high glucose concentrations (33.3-100 g/l). Conversely, Vaario et al (2002) discussed that carbon transfer may be low via the mycorrhizae compared to their experimental results.…”
Section: Discussionmentioning
confidence: 99%